Mobile Banking - Ways to Develop a Modern Banking Service - Anvarovich, Nozimov Eldor (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This article describes in detail the formation of "Mobile banking" as a modern banking service, its role and importance in the organization of banking services. It has been revealed that mobile banking is one of the foundations for banks to enter the new system and its advantages. The possibilities of remote banking services provided through the Mobile banking application were also presented, as well as the risks in this process. In addition, the reforms being implemented in the country to further improve the quality of customer service of banks and the convenience created for the population to use banking services were analyzed. Also, scientific and practical recommendations on the areas of further development and improvement of remote banking services provided by banks through mobile banking applications and improving their quality were proposed.